(untitled) (Global Journal of Human-Social Science, 2020)
This is a collaborative action research design which focused on using classroom management as a strategy to curbing disruptive behaviours among 5th Grader learners at Ridge Experimental School in Akim-Oda in the Birim Central Municipality of the Eastern region of Ghana. Though the study appeared experimental and descriptive in nature, the concurrent mixed method research approach informed its direction. Questionnaires, interviews tests and observation were the primary data collection tools. Descriptive, interpretive and interaction process analyses were used to analyse all data gathered. Accidental and simple random sampling techniques were involved in the selection process. The study revealed personality disorder, economic and social factors, lack of interests in classroom lessons among others result in disruptiveness in school whereas creating a positive and engaging classroom atmosphere, ensuring appropriate seating arrangement, development of class routine chart and good choice of methodologies can help curb disruptiveness in the classroom and beyond.